2017
DOI: 10.1073/pnas.1718441115
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic anti-HCV broadly neutralizing human monoclonal antibodies with independent mechanisms

Abstract: There is an urgent need for a vaccine to combat the hepatitis C virus (HCV) pandemic, and induction of broadly neutralizing monoclonal antibodies (bNAbs) against HCV is a major goal of vaccine development. Even within HCV genotype 1, no single bNAb effectively neutralizes all viral strains, so induction of multiple neutralizing monoclonal antibodies (NAbs) targeting distinct epitopes may be necessary for protective immunity. Therefore, identification of optimal NAb combinations and characterization of NAb inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 51 publications
3
46
0
Order By: Relevance
“…This work demonstrates that entry occurs via a two-phase process, in the first of which HCV forms a tripartite receptor complex with SR-B1, CD81 and EGFR at the basolateral surface. Numerous other studies have assessed HCV entry kinetics using time of addition inhibitor studies; these experiments suggest that SR-B1 functions immediately after virus attachment, and likely precedes CD81 engagement [12,36,37]. Furthermore, multiple reports have been made of a minority fraction of infection that persists despite targeting of SR-B1 with CRISPR, siRNA or antibody blockade [35,37,48,49], supporting the notion of an SR-B1-independent mode of entry.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This work demonstrates that entry occurs via a two-phase process, in the first of which HCV forms a tripartite receptor complex with SR-B1, CD81 and EGFR at the basolateral surface. Numerous other studies have assessed HCV entry kinetics using time of addition inhibitor studies; these experiments suggest that SR-B1 functions immediately after virus attachment, and likely precedes CD81 engagement [12,36,37]. Furthermore, multiple reports have been made of a minority fraction of infection that persists despite targeting of SR-B1 with CRISPR, siRNA or antibody blockade [35,37,48,49], supporting the notion of an SR-B1-independent mode of entry.…”
Section: Discussionmentioning
confidence: 93%
“…Whereas the CD81 binding site is composed of discontinuous protein domains that are bought together in the tertiary structure of E2 and interact with the large extracellular loop of CD81 [5,11]. Strain specific and broadly neutralising antibodies, which develop during natural infection, act by blocking E2-SR-B1/CD81 interactions [12][13][14][15]. A deeper understanding of E2 function and its interactions with SR-B1 and CD81 is likely to aid the design of candidate B-cell targeted vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of a B cell-based vaccine is to induce responses that protect from multiple virus genotypes and subtypes. In this cohort, plasma samples with bNAb activity were enriched for multi-epitope responses, particularly directed towards AR2, AR3, AR4 and domain D. Interestingly, these combinations were recently shown by 2 independent reports to have synergistic activity in vitro, 11,32 which was superior to individual mAb activities. This supports a recent paper by Kinchen and colleagues, 33 who reported that the induction of AR3 or domain D targeting bNAbs may be important in developing an effective NAb response in combination with AR4-targeting bNAbs.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that neutralizing antibodies are associated with spontaneous clearance of HCV infection and reinfection. [264][265][266][267] HCV accounts for 85-95% of mixed cryoglobulinemia, a common extrahepatic manifestation of HCV. The cryoglobulinemia occurs by HCV antigen-driven B cell clonal proliferation leading to the deposition of circulating immune complexes in small vessels of the skin, nerves, kidney, liver, and joints.…”
Section: B Cell Responsementioning
confidence: 99%